Development of Website-Based Teaching Materials to Improve Historical Understanding in History Learning for Class X Students of SMA Negeri 1 Rangkat - Imory S, Amadhea Clarita; Ahmal, Ahmal; Asril, Asril (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research discusses the development of website-based teaching materials to improve understanding of history in history learning for class X students at SMA Negeri 1 Rangkat. The aim of this research is to determine the development of website-based teaching material design, determine the feasibility of developing website-based teaching materials, and understand history by using website-based teaching materials in history learning for class This research uses a Research and Development (RD) approach, namely an approach that produces and develops a physical product that has been tested for feasibility and effectiveness. Implementation of the RD approach using the PIE (Plan, Implement and Evaluate) development model. The results of this research show that the number of assessments given by media experts is 71 while the percentage obtained is 90% and the validation value is in the "Very Appropriate" category, the material expert assessment is 58 with the percentage obtained is 95.4% and is included in the "Very Good" category. Eligible", the validation score for the Pretest-Posttest questions by the teacher was 144 with a percentage of 96% so it was included in the "Very Appropriate" category and the students' understanding score after using the product was based on the results of the pre-test and post-test, the small group got a pre-test result of 29.1 and posttest 75. While the large group got pre-test results of 34.35 and post-test 76.45, there was an increase in scores after teaching and learning activities using website-based teaching materials and based on the results of pre-test and post-test participants' understanding students have reached the level of analysis.